Предмет: Алгебра, автор: dilnaz1404

Преобразовать дробь в выражение
1 и 2 пример

Приложения:

Ответы

Автор ответа: NNNLLL54
3

1)\; \; \frac{b}{(a-b)^2}-\frac{a+b}{b^2-ab}=\frac{b}{(a-b)^2}-\frac{a+b}{-b(a-b)}=\frac{b^2+(a+b)(a-b)}{b(a-b)^2}=\\\\=\frac{b^2+a^2-b^2}{b(a-b)^2}=\frac{a^2}{b(a-b)^2}

2)\; \; \frac{a}{a-6}-\frac{3}{a+6}+\frac{a^2}{36-a^2}=\frac{a}{a-6}-\frac{3}{a+6}+\frac{a^2}{-(a-6)(a+6)}=\\\\=\frac{a(a+6)-3(a-6)-a^2}{(a-6)(a+6)}=\frac{a^2+6a-3a+18-a^2}{(a-6)(a+6)}=\frac{3a+18}{(a-6)(a+6)}=\\\\=\frac{3\, (a+6)}{(a-6)(a+6)}=\frac{3}{a-6}

Похожие вопросы
Предмет: Математика, автор: butorinaa85